Agriculture, nutrition, and the Green Revolution in Bangladesh - Headey, Derek D.; Hoddinott, John F. (International Food Policy Research Institute, 2015)
This paper therefore analyzes agriculture and nutrition linkages in Bangladesh, a country that achieved rapid growth in rice productivity at a relatively late stage in Asia’s Green Revolution, as well as unheralded progress against undernutrition. To do so the authors create a synthetic panel that aggregates nutritional data from five rounds of the Demographic Health Surveys (1997 to 2011) with district-level estimates of rice yields. Using various panel estimators, they find rice yields significantly explain weight gain in young children but not linear growth. The authors further show that rice yields have large and positive effects on the timely introduction of complementary foods for young children but not on dietary diversity indicators and that this complementary feeding indicator is positively associated with child weight gain but not with linear growth.